2002
DOI: 10.1136/fn.86.2.f124
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the subarachnoid space by ultrasound in preterm infants

Abstract: Background: Measurements of the subarachnoid space during routine cranial sonography may provide an indirect method of monitoring brain growth in preterm infants. Methods: The width of the subarachnoid space was measured on coronal views during head sonography. Initial scans (within five days of birth) were compared with follow up scans. Results: A total of 361 scans were performed on 201 preterm infants. The mean width of the subarachnoid space was < 3.5 mm for 95% of initial scans. It was slightly larger in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 13 publications
4
38
1
Order By: Relevance
“…In this study, the difference between initial and follow up scans suggested reduced brain growth in extrauterine preterm babies. 62 Another study confirmed the relationship between gestational age and transverse cerebellar diameter. 63 Doppler ultrasound parameters can serve as a tool for predicting developmental delay.…”
supporting
confidence: 52%
“…In this study, the difference between initial and follow up scans suggested reduced brain growth in extrauterine preterm babies. 62 Another study confirmed the relationship between gestational age and transverse cerebellar diameter. 63 Doppler ultrasound parameters can serve as a tool for predicting developmental delay.…”
supporting
confidence: 52%
“…Two different studies found a close correlation between head circumference and brain development; however they reported that SAS measurements may be more valuable than head circumference measurements (12,15). In our study the SAS and VW values of mature-premature newborns were in accordance with head circumference values and larger in mature newborns.…”
Section: Resultssupporting
confidence: 76%
“…The initial mean SAS value was 1.56 mm, with mean at 36 weeks 1.94 mm and a weekly increase of 0.02 mm reported (12). In this study, the distance of the CC of the SAS was measured between 1.34-2.22 mm in premature newborn and was similar to previous studies.…”
Section: Resultssupporting
confidence: 73%
“…2 Head circumference measurement has a low interrater agreement and limited association with longterm outcome and does not measure actual brain growth, but growth of the skull and the subarachnoid spaces, which are frequently enlarged in preterm infants. 5,6,25 Measurement of CCF length is not considered a burden compared with head circumference measurement because it can be performed on routine CUS, which is often recommended weekly in preterm infants. 26 Both CCF length and CC length can already be measured prenatally because the CC and the fastigium are visible on sonography at around 18 weeks of gestation; this feature allows the use of the same marker prenatally and postnatally for monitoring of brain growth.…”
Section: Discussionmentioning
confidence: 99%